Effective Strategy: Talking Stick Cooperative Learning to Improve Understanding of Chemical Bonding - Sopiatun Sopiatun; Hassan Abdullahi Dachia; Vida Khojasteh (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to evaluate the effectiveness of implementing the Talking Stick Cooperative Learning Model in improving the learning outcomes of Class X2 students at Rangsang 1 State Senior High School, located in Rangsang District, Meranti Islands Regency, on the topic of Chemical Bonds. Methodology: This study is a Classroom Action Research. The subjects of the study were 38 students of Class X2 at Rangsang 1 State Senior High School, located in Rangsang District, Meranti Islands Regency, consisting of 24 male students and 14 female students. The instruments used were learning activity tools and student learning outcome tests. The data analysis technique in this study employed descriptive analysis. Main Findings: Based on data analysis, the students' learning mastery before the intervention was 53.95, which increased to 64.74 in Cycle I, 73.42 in Cycle II, and 79.47 in Cycle III, showing a significant improvement. Thus, the data analysis results conclude that the implementation of the Talking Stick Cooperative Learning Model can enhance the chemistry learning outcomes of Class X2 students at Rangsang 1 State Senior High School, Rangsang District, Meranti Islands Regency. Novelty/Originality of this study: This study provides novel insights into the effectiveness of the Talking Stick Cooperative Learning Model in significantly enhancing student learning outcomes in chemistry, particularly on the topic of chemical bonds, within the context of a rural high school setting.